Physical Activity Levels and Mental Illness Risk in Elderly Women during COVID-19 - Encarnação, Samuel Gonçalves Almeida da (2022)
This research aimed to verify the effect of the COVID-19 pandemic on mental illness risk (MIR) and confirm the association of PA levels with MIR in elderly women during the COVID-19 pandemic. This experimental longitudinal study involved 44 elderly women aged 67.3± 5.3 years. The SRQ-20 and IPAQ were applied from February 2020 to February 2021, prior to the onset and during the pandemic. Significant increase (242%) of positive responses to MIR between the two periods (p= 0.002, February: 7 vs August: 17, (X2 (1)= 8.51; p= 0.003, RR= 3.02). Regarding PA levels, there was a significant increase (566%) with a large effect size (ES) in the number of elderly women with low PA levels, from 3 in February to 20 in August, p= 0.0001, V= 1. There was a significant reduction (450%) with high ES of 18 elderly women with high levels of PA from February to 4 in August, p= 0.0001, V= 1. An inverse correlation was identified, with moderate ES between the levels of MIR and PA during the pandemic, r= -0.40, R2= 0.16. The COVID-19 pandemic caused an increase in the MIR of elderly women with a moderate inverse association with PA levels during the COVID-19 pandemic.